2002
DOI: 10.1007/pl00013196
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal isotopic shifts in fish of the Pantanal wetland, Brazil

Abstract: Seasonal inundations shape the floodplain characteristics of the Pantanal, a large wetland in Central South America. In the first study combining stable carbon and nitrogen isotope analysis with classical stomach content analysis in this region, we investigated the influence of the annual inundation on diet and isotopic composition of floodplain fish. Apart from potential food items, 33 fish species from the Coqueiro Lake were analyzed, 10 of which were present during both the wet and dry season 1999. A d 13 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
2
24

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(170 citation statements)
references
References 38 publications
9
135
2
24
Order By: Relevance
“…Therefore, the large variation in δ 15 N values for the invertivorous fish species that dominated the San Pedrito Lagoon food web could be due to consuming different proportions of terrestrial and aquatic insects. Wantzen et al (2002) observed a comparable amount of variation in δ 15 N values of invertivorous fish species in the Pantanal, and suggested that such variation may be due to differences in consumption of aquatic and terrestrial resources, especially as influenced by seasonal flooding. Zeug & Winemiller (2008) found riparian vegetation to be the dominant carbon source utilized in food webs of a temperate floodplain river system, with invertebrates as the pathway by which riparian-derived carbon entered the aquatic food web.…”
Section: Centropomus Undecimalis Diapterus Auratus Eugerres Plumiermentioning
confidence: 91%
“…Therefore, the large variation in δ 15 N values for the invertivorous fish species that dominated the San Pedrito Lagoon food web could be due to consuming different proportions of terrestrial and aquatic insects. Wantzen et al (2002) observed a comparable amount of variation in δ 15 N values of invertivorous fish species in the Pantanal, and suggested that such variation may be due to differences in consumption of aquatic and terrestrial resources, especially as influenced by seasonal flooding. Zeug & Winemiller (2008) found riparian vegetation to be the dominant carbon source utilized in food webs of a temperate floodplain river system, with invertebrates as the pathway by which riparian-derived carbon entered the aquatic food web.…”
Section: Centropomus Undecimalis Diapterus Auratus Eugerres Plumiermentioning
confidence: 91%
“…These increases can, at least partially, result from the input of terrestrial material through the transport of terrestrial invertebrates (e.g., ants, spiders, grasshoppers) with the wind and flood waters into the waterways, where they subsidize the diets of carnivorous fish. These invertebrates can be of crucial importance to those fish diets (Nakano andMurakami 2001, Sullivan et al 2012), and seasonal variations in this importance have been reported for other tropical areas (e.g., Wantzen et al 2002, Balcombe et al 2005.…”
Section: Mixing Modelsmentioning
confidence: 98%
“…Rivers and estuaries are subjected to high human pressure, as their settings make them ideal for human settlement. This pressure has been intensified over the last century, especially in tropical areas where increasing population numbers place increasing pressure on these environments (Junk 2002). Impacts such as deforestation, urbanisation, agriculture and flow regulation can directly affect the energetic connectivity between land and rivers, and these impacts can be transported downstream to the estuaries.…”
Section: Introductionmentioning
confidence: 99%
“…As water-level fluctuates, the organic matter from terrestrial or macrophyte plants also may represent a large proportion of the basal food sources of floodplain lakes (Wantzen et al 2002;Wang et al 2011Wang et al , 2012. Major nitrogen cycling processes, such as nitrogen fixation, nitrification, and denitrification, which exert strong effects on isotopic fractionation during nitrogen transformation, also vary between dry and wet seasons (Hadas et al 2009).…”
Section: Decreases In Dmentioning
confidence: 99%